Paraquat induced pulmonary fibrosis in three survivors. Issue 3 (March 1991) - Hudson, M; Patel, S B; Ewen, S W; Smith, C C; Friend, J A
Abstract : Pulmonary lesions following paraquat poisoning are believed to be almost invariably fatal. The three patients reports here survived despite persistent radiological change. One of the patients died after taking a larger dose of paraquat one year later, and at necropsy histological changes attributable to the two episodes of paraquat poisoning were apparent.